Impact of Demographic Transition on the Trade Balance of Pakistan: An Econometric Analysis (Journal of Asian Development Studies, 2020)
This study investigated whether a stable long run relationship exists between demographic transition and trade deficit in Pakistan over the period 1981 to 2012. Trade balance is defined as the difference between exports and imports of goods and services. To achieve this objective, Augmented Dickey Fuller unit root test is applied in order to determine the integrated order of the selected variables.  Engel Granger cointegration technique is employed to estimate the long run equilibrium relationship as all the variables have same integration order. Different diagnostics such as Ramsey RESET test and stability tests such as CUSUM and CUSUMSQ are applied to test the model specification and stability of estimated model. The estimation and stability tests results suggest that there exists stable long run relationship between trade deficit and its determinants in Pakistan. Population growth, Term of Trade are the main determinants of money demand behavior in Pakistan. This results of the study are useful for public policy as well as fiscal policy. Pakistan economy thus demands for pro public policies in the economy to have political, social and economic stability in the country.